Simulation and Design of a PCB-Chassis System for Reducing Radiated Emissions - Park, Hyun Ho; Jangq, Hyun-Tae; Park , Hark-Byeong (Applied Computational Electromagnetics Society Journal (ACES), 2022)
The effects of the design parameters for a printed circuit board (PCB)-chassis system such as the slots on the chassis, the decoupling capacitors on the PCB, and the grounding posts (screws) connected between the PCB and the chassis are investigated using numerical analysis. These design parameters can affect the radiated emissions of the PCB-chassis system by changing or removing the resonances of the PCB and chassis. This numerical investigation represents a promising guideline for optimizing the number and location of grounding posts with regard to the placement of slots on a chassis and of decoupling capacitors on a PCB. The simulated results are shown to be consistent with the corresponding theoretical interpretations. Several design guides are summarized in the conclusion.